Using digital media resources to train future education managers - Тапалова, Ольга; Куатбеков , Асхат (Pedagogy and Psychology, 2021)
This article highlights the topic of using digital media resources in training specialists - future education managers. At the present stage, the relevance of training future education managers is important for improving the quality of educational services in educational institutions. Research methods: theoretical analysis, methods of questioning and survey among students and teachers. The article presents the obtained experimental data on the study of the development of creative thinking of future education managers. The analysis was made of modern teaching methods, common to which is the focus on self-education through open access and media resources to information. The most popular at the moment are video materials, presentations. Little coverage in the educational process of the university is given to the topic of online libraries. Online libraries are an important part of education and contain a large amount of scientific data. The survey revealed that only 32% of students - future education managers are familiar with online libraries. The development of creative thinking should be a priority in the training of future managers of the secondary and higher education system.